The mediating role of e-behavior in the relationship between the electronic word of mouth and electron-ic decision of purchas - Khaled Abdel Kader Alomari (International Journal of Data and Network Science)
The current research aims to recognize the mediating role effect of the e-behavior (henceforth e-behavior) on the relationship between the electronic word of mouth (henceforth e-WOM) and the electronic decision of purchase (henceforth e-DOP) among the students of Jadara University/ Jordan. The research adopted a descriptive analytical methodology in data collection and analyses; and developed a questionnaire to measure the variables of e-behavior, e-WOM, and e-POD. Students using the university Facebook website completed the questionnaire, 400 retrieved questionnaires were valid for statistical analysis. Smart PLS software was used to analyze the collected data. The study found statistical differences of e-WOM on the e-DOP, significant differences were also found of e-behavior in the relationship between e-WOM and e-DOP. The study recommends companies to take interest in e-WOM and to add it to its marketing strategies, because e-WOM effects taking an e-DOP by potential customers and enhances positive purchase behavior.